THE OUTCOMES OF FUNCTIONING OF THE UNIFIED SYSTEM OF INDIVIDUAL DOSE CONTROL OF THE RUSSIAN FEDERATION CITIZENS BASED ON THE 2015 DATA - A. N. Barkovsky; R. R. Akhmatdinov; N. K. Baryshkov; A. A. Bratilova; T. A. Kormanovskaya; S. I. Kuvshinnikov; L. V. Repin; I. P. Stamat; O. E. Tutelyan (Радиационная гигиена, 2017)
The article presents the outcomes of the generalized analysis of personnel, patients, and population radiation doses information obtained from the Unified System of Individual Dose Control (USIDC) for 2015. The analysis is conducted on the basis of the annual information from the forms of Federal State Statistical. Observation No.1-DOZ (personnel individual doses), No.2-DOZ (emergency doses), No.3-DOZ (patients’ exposure doses) and No.4-DOZ (population exposure doses from natural and technogenically impacted background). The information is submitted by the organizations and territories accountable to the Rospotrebnadzor. The article presents a comparison with data obtained within the framework of Radiation-Hygiene passportization. In 2015, 16769 organizations providing management with artificial radiation sources submitted the form No.1-DOZ.The form No.1-DOZ contains data on 134 812 personnel individual doses, 123 404 of the personnel group A and 11 408 the personnel group B with personnel monitoring.Iin 2015,the average individual dose for the personnel group A was 1,14 mSv, the personnel group B – 0,79 mSv. In 2015, 11 720 healthcare organizations submitted the form No.3-DOZ. According to the No.3-DOZ data, more than 272 mln X-ray diagnostics were conducted in theRussian Federation in 2015. An average medical radiation dose per capita was 0,48 mSv/year and a mean medical radiation dose per an X-ray examination was 0,26 mSv. In 2015, the form No.4-DOZ contains results of 8 681 measurements of gamma dose rate in wooden houses, 12 642 measurements in one-storey stone houses, 160 174 measurements in multi-storey stone houses and 217 746 measurements on the open ground. Results of 4 441 measurements of radon concentration levels in wooden houses, 5 565 measurements in one-storey stone houses, 61 541 measurements in multi-storey stone houses are given. The population’s average effective dose from natural ionizing radiation sources amounted to 3.44 mSv/year, the average values for the subjects of the Russian Federation fall in the range from 1,6 mSv/year (Sakhalin Oblast) to 11,4 mSv/year (Jewish Autonomous Oblast). The article includes the Annexes with the final generalized forms of the Unified System of Individual Dose Control in 2015 based on the forms of statistical observations No. 1-, 3- and 4-DOZ